2015
DOI: 10.1039/c4ob02364a
|View full text |Cite
|
Sign up to set email alerts
|

LNA units present in the (2′-OMe)-RNA strand stabilize parallel duplexes (2′-OMe)-RNA/[All-RP-PS]-DNA and parallel triplexes (2′-OMe)-RNA/[All-RP-PS]-DNA/RNA. An improved tool for the inhibition of reverse transcription

Abstract: Homopurine phosphorothioate analogs of DNA, possessing all phosphorus atoms of RP configuration ([All-RP-PS]-DNA), when interact with appropriate complementary RNA or (2'-OMe)-RNA templates, form parallel triplexes or parallel duplexes of very high thermodynamic stability. The present results show that T-LNA or 5-Me-C-LNA units introduced into the parallel Hoogsteen-paired (2'-OMe)-RNA strands (up to four units in the oligomers of 9 or 12 nt in length) stabilize these parallel complexes. At neutral pH, dodecam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…Additionally, when LNA units were introduced in the 2’-O-Me RNA strand, the stabilizing effect was measurably stronger. These results are in accordance with data in the literature [ 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, when LNA units were introduced in the 2’-O-Me RNA strand, the stabilizing effect was measurably stronger. These results are in accordance with data in the literature [ 35 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are supported by the findings of Kierzek's group . The same trend was observed in reverse transcription experiments, where the inhibition of the process by parallel triplexes with LNA moieties was more efficient than unmodified structures . Maciaszek et al .…”
Section: Parallel Dna and Rna Duplexessupporting
confidence: 79%
“…In 2015, Guga's group reported that LNAs located in the 2′‐ O ‐methyl‐RNA strand enhanced the stability of parallel duplexes . The increase in thermodynamic stability of these structures correlates with the frequency of LNAs.…”
Section: Parallel Dna and Rna Duplexesmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 It should be noted that a few years ago phosphorothioation of DNA in bacteria was discovered. 7,9,10 † Dedicated to Professor Andrzej Okruszek (Technical University of Lodz) on the occasion of his 70th birthday. 6 To achieve the desired stronger hybridization, one has to introduce more altering modifications into the sugar-phosphate backbone.…”
Section: Introductionmentioning
confidence: 99%